Jak umiera pisarz? Śmierci urojone (Morts Imaginaires) Michaela Schneidera jako nekrofikcje - Thiel-Jańczuk, Katarzyna (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2012)
The starting point of Michel Schneider’s Morts imaginaires, which refers to Vies imaginaires of the Belgian symbolist writer Marcel Schwob, is ultima verba, i.e. the last words that could probably be said by dying writers in various times. However, by choosing to talk about them from the perspective of death, the French author does not want to participate in the “necrographical”, offi cial discourse of a writer’s death or in the biographical (historical) discourse, which do not respect the personal and singular experience of death. In this way, literary fi ction about the experience of dying, which is here called “necrofi ction” and which is legitimized by a psychoanalytic approach to the imaginary, becomes an alternative to the official forms of discourse about death or life.